Gower handbook of customer service - Murley, Peter (Gower, 1996)
In a world dominated by look-alike products at similar prices, superior customer service may be the only available route to competitive advantage. This Gower Handbook brings together no fewer than 33 professionals in the field, each one a recognized expert on his or her subject. Using examples and case studies from a variety of businesses, they examine the entire range of customer service activities, from policy formulation to telephone technique